The development of an enzyme linked immunosorbent assay for the detection of the South African strain(s) of grapevine fanleaf nepovirus - Liebenberg, Annerie (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Genetics))--Stellenbosch University, 2008.